STRATEGI PENINGKATAN CAPAIAN IKU-2 PADA PROGRAM MBKM DI PROGRAM STUDI PENDIDIKAN BIOLOGI UNIVERSITAS PALANGKA RAYA - Titin Purnaningsih; Rahmadyah Kusuma Putri; Sugeng Mashabhi; Karina Evaying; Irena Stephani Ambarita (Idaarah: Jurnal Manajemen Pendidikan, 2023)
Indikator Kinerja Utama (IKU) are performance measures to create an adaptive university with more concrete outcomes. This policy accelerates the implementation of the MBKM Program. Universities are required to implement a curriculum adapted to MBKM to achieve IKU-2. The Universitas Palangka Raya is not optimal in IKU-2, which is still below the standard of 0.05% (9/16,920) in 2020 and 1.89% (250/13,207) in 2021. The Biology Education Study Program as one of the Study Programs those who contribute to IKU-2 certainly need a strategy to increase IKU-2 achievements in the MBKM Program. This research is a qualitative research. Respondents totaled 30 people consisting of Head of Study Program, Students, Lecturers and Staff of Biology Education. Data collection was carried out by means of semi-structured interviews, observations, and questionnaires. Research data were analyzed using SWOT and QSPM analysis. Based on the results of the analysis, an alternative strategy was obtained to increase IKU-2 achievements, namely the strategy of integrating the MBKM program with lecturer project research assistance activities.